2013
DOI: 10.1074/jbc.m113.478800
|View full text |Cite
|
Sign up to set email alerts
|

Autoactivation of Mouse Trypsinogens Is Regulated by Chymotrypsin C via Cleavage of the Autolysis Loop

Abstract: Background: Hereditary pancreatitis-associated mutations alter regulation of trypsinogen activation by chymotrypsin C. Results: Activation of mouse trypsinogens T8 and T9 is inhibited by chymotrypsin C-mediated cleavage of the autolysis loop. Conclusion: Chymotrypsin C regulates activation of human and mouse trypsinogens by different mechanisms. Significance: Introduction of human pancreatitis-associated mutations into mouse trypsinogens will not recapitulate the pathogenic biochemical effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 34 publications
(38 reference statements)
1
39
0
Order By: Relevance
“…51 and Fig. 1), mutation p.R122H had no appreciable effect on the autoactivation of T8 trypsinogen in the presence of mouse Ctrc (36). These observations argue that human pancreatitis-associated mutations may not recapitulate the pathogenic biochemical phenotype in the context of mouse trypsinogens.…”
Section: Animal Models Of Prss1 Related Pancreatitismentioning
confidence: 66%
See 1 more Smart Citation
“…51 and Fig. 1), mutation p.R122H had no appreciable effect on the autoactivation of T8 trypsinogen in the presence of mouse Ctrc (36). These observations argue that human pancreatitis-associated mutations may not recapitulate the pathogenic biochemical phenotype in the context of mouse trypsinogens.…”
Section: Animal Models Of Prss1 Related Pancreatitismentioning
confidence: 66%
“…Nevertheless, this study focused attention to the question whether the biochemical effects human PRSS1 mutations would be similar in the context of mouse and human trypsinogens and whether we can make use of mouse trypsinogens to model the human disease. Recently, we demonstrated that the mouse pancreas expresses four trypsinogen isoforms to high levels (T7, T8, T9, and T20), and mouse Ctrc strongly inhibits autoactivation of isoforms T8 and T9 through cleavage of the autolysis loop (36). In sharp contrast to the human situation (see Ref.…”
Section: Animal Models Of Prss1 Related Pancreatitismentioning
confidence: 98%
“…The pancreas is the major source of proteases in the digestive system for breaking down ingested proteins and the proteases play a central role in the digestive process (Whitcomb and Lowe 2007). Of the three positively selected protease genes that were identified, CTRC and PRSS1 enzymes are secreted from the pancreas: CTRC is a proteolytic regulator of trypsinogen auto activation which cleaves the trypsinogen activation peptide to stimulate auto activation (Németh et al 2013), and PRSS1 enzyme cleaves internal bonds involving the carboxyl group of lysine or arginine and activates other pancreatic proenzymes (Whitcomb and Lowe 2007). The third positively selected protease gene from the intestine is the serine proteinase, TMPRSS15 (also known as PRSS7 ) encoding enterokinase, that activates trypsinogen to trypsin which in turn activates other proenzymes including chymotrypsinogen, procarboxypeptidases, and proelastases (Imamura and Kitamoto 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A BAC transgene conferred high levels of human PRSS1 R122H expression. Based on our experience with genetically engineered mouse models and recent advancements in understanding of the biochemical characteristics of mouse and human PRSS1 pioneered by Sahin-Toth (26)(27)(28), we reasoned that both the species and expression level of the PRSS1 gene were critical for successfully modeling the disease in mice. Therefore, we decided to use a human bacterial artificial chromosome (BAC) harboring the full-length Currently, an effective targeted therapy for pancreatitis is lacking.…”
Section: Resultsmentioning
confidence: 99%